Plasma activated eb-deposition: different modes of arc discharge and plasma characteristics - Safonov, V. (Вопросы атомной науки и техники, 2017)
The results of experimental study of the operating parameters of a non-self-sustaining arc discharge in the process of electron-beam evaporation of a cathode are presented in the paper. The conditions of ignition and burning of the arc discharge were studied. The plasma parameters, ion current on the substrate, and current-voltage characteristic of the discharge in Cr and Ti vapors are investigated depending on the electron beam power. It was shown that thermionic emission mechanism is not capable for providing of charge transfer on the cathode surface. The different arc modes are realized in the process of cathode heating by a focused electron beam. The arc can be permanently stable in two modes depending on the power of the electron beam. The regime of diffuse binding of the cathode spot is realized at beam power of more than 2.5 kW. At a lower power regime, a contracted spot is existed in the region of cathode heating by electron beam. Представлені результати експериментального дослідження робочих параметрів несамостійного дугового розряду в процесі електронно-променевого випаровування катода. Вивчені умови запалювання і горіння дугового розряду. Досліджені вольт-амперні характеристики розряду в парах Cr і Ti, параметри плазми, іонний струм на підкладку в залежності від потужності електронного променя. Показано, що такий механізм, як термоелектронна емісія, не здатний забезпечити перенесення заряду на поверхні катода. Встановлено, що при нагріванні катода сфокусованим електронним променем реалізуються різні режими дугового розряду. Залежно від потужності електронного променя дуга може стійко існувати в двох режимах: при потужності променя більше 2,5 кВт – з дифузною прив'язкою катодної плями, а при меншій потужності – з контрагірованою плямою, яка існує в області нагріву катода електронним променем. Представлены результаты экспериментального исследования рабочих параметров несамостоятельного дугового разряда в процессе электронно-лучевого испарения катода. Изучены условия зажигания и горения дугового разряда. Исследованы вольт-амперные характеристики разряда в парах Cr и Ti, параметры плазмы, ионный ток на подложку в зависимости от мощности электронного луча. Показано, что механизм термоэлектронной эмиссии не способен обеспечить перенос заряда на поверхности катода. Установлено, что при нагреве катода сфокусированным электронным лучом реализуются различные режимы дугового разряда. В зависимости от мощности электронного луча дуга может устойчиво существовать в двух режимах: при мощности луча более 2,5 кВт – с диффузной привязкой катодного пятна, а при меньшей мощности – с контрагированным пятном, существующим в области нагрева катода электронным лучом.